The Correlation of Sentence Structure Knowledge and Vocabulary Mastery with Narrative Text Writing Ability in The Middle School Students - Ni Nyoman Rai Rohani (IJLHE: International Journal of Language, Humanities, and Education, 2018)
This study aims to determine the relationship between sentence structure knowledge and vocabulary mastery with the ability to write narrative texts for class nineth students of SMPN 2 Bandar Mataram. To achieve the research objectives mentioned above, the authors use the correlational method, meaning that data is collected after all the events in question take place. The technique used in collecting research data is an objective test (multiple choice) and a subjective test (written). Research data analysis techniques include normality test, statistical analysis, and research hypothesis testing techniques. Based on the results of the study, it can be concluded that, (1) there is a positive and significant relationship between vocabulary mastery and the ability to write narrative texts, as indicated by a correlation coefficient of 0.598 and a coefficient of positive 0563 (2) there are a positive and significant relationship between knowledge of sentence structure as indicated by a correlation coefficient of 0589 (3) there is a positive and significant relationship between vocabulary and mastery of sentence structure as indicated by the correlation coefficient is 0217.